2020
DOI: 10.3389/fendo.2020.00431
|View full text |Cite
|
Sign up to set email alerts
|

Does Hashimoto's Thyroiditis Increase the Risk of Cardiovascular Disease in Young Type 1 Diabetic Patients?

Abstract: Głowinska-Olszewska et al. Diabetes, Hashimoto's Thyroiditis, and Cardiovascular Risk Conclusions: Young patients with type 1 diabetes mellitus and with coexisting Hashimoto's thyroiditis have a higher BMI, a higher waist circumference, and a higher HbA 1 c value, which altogether may cause faster development of macroangiopathy in the near future. Additional risk for cardiovascular disease may result from low vitamin D and increased hsCRP concentration in this group of patients. Coexistence of Hashimoto's thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
12
1
1
Order By: Relevance
“…The epidemiology and risk factors for microvascular and macrovascular complications in T1D patients have been extensively studied [7,8,9], but less attention has been paid to the presence of comorbid AIDs and their impact on the presence of complications. Additional autoimmune diseases may negatively affect metabolic control in patients with T1D [10,11], thereby potentially increasing the risk of micro or macrovascular complications. Furthermore, most autoimmune diseases confer an increased risk of cardiovascular disease [12,13], which could add to the already high baseline cardiovascular risk of T1D.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology and risk factors for microvascular and macrovascular complications in T1D patients have been extensively studied [7,8,9], but less attention has been paid to the presence of comorbid AIDs and their impact on the presence of complications. Additional autoimmune diseases may negatively affect metabolic control in patients with T1D [10,11], thereby potentially increasing the risk of micro or macrovascular complications. Furthermore, most autoimmune diseases confer an increased risk of cardiovascular disease [12,13], which could add to the already high baseline cardiovascular risk of T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these factors are overproduced with obesity. Conversely, levels of adiponectin are downregulated during obesity ( Tschritter et al, 2003 ; Lihn et al, 2005 ; Hajri et al, 2017 ; Głowinska-Olszewska et al, 2020 ; Skorepa et al, 2020 ). Wang et al’s (2019) results showed that high adiponectin is associated with stroke severity and support the hypothesis that adiponectin can serve as a biomarker of poor outcome after stroke, independent of baseline variables.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of stroke and myocardial infarction is 1.63 and 1.46 in T1D with AT and 1.28 and 1.33 in T1D with CD. The molecular mechanisms underlying this synergy are not yet known, although the chronic inflammation that characterizes autoimmune diseases has been partly held responsible [ 6 , 7 ]. From this perspective, patients with concomitant autoimmune diseases should receive a more intensive multifactorial treatment to prevent acute clinical events.…”
Section: Introductionmentioning
confidence: 99%